2008
DOI: 10.1165/rcmb.2007-0172oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KGF on Alveolar Epithelial Cell Transdifferentiation Are Mediated by JNK Signaling

Abstract: Rat alveolar epithelial cells (AEC) in primary culture transdifferentiate from a type II (AT2) toward a type I (AT1) cell-like phenotype, a process that can be both prevented and reversed by keratinocyte growth factor (KGF). Microarray analysis revealed that these effects of KGF are associated with up-regulation of key molecules in the mitogen-activated protein kinase (MAPK) pathway. To further explore the role of three key MAPK (i.e., extracellular signal-related kinase [ERK] 1/2, c-Jun N-terminal kinase [JNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…Previous studies have shown that AQP5 is a marker of AECI, and SP-C is a marker of AECII (6,10). In the present study, our evaluation showed that KGF promoted transdifferentiation of AECIIs, as well as making AECIs revert to AECIIs.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous studies have shown that AQP5 is a marker of AECI, and SP-C is a marker of AECII (6,10). In the present study, our evaluation showed that KGF promoted transdifferentiation of AECIIs, as well as making AECIs revert to AECIIs.…”
Section: Discussionsupporting
confidence: 69%
“…It is well established that alveolar epithelial type II cells (AECIIs) serve to defend the alveoli, and their functions include synthesis and secretion of pulmonary surfactant, activation of ion transport, and maintenance and repair of alveolar epithelium after lung injury (6). Primary AECIIs cultured over a period of 3 to 4 days gradually transdifferentiate to alveolar epithelial type I cells (AECIs).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, fibroblasts reside beneath alveolar lung epithelia and make contact with ATI and ATII cells through gaps within the basement membrane (11). Fibroblasts secrete important soluble factors (e.g., keratinocyte growth factor [KGF]) that have been reported to limit transdifferentiation and to promote ATII cell proliferation (11)(12)(13)(14)(15). ATII cells cocultured with human or rat fibroblasts or exposed to KGF exhibit surfactant mRNA expression in vitro for extended periods, suggesting that KGF (added or presumably secreted by fibroblasts) was in part responsible for retaining ATII cell differentiation in vitro (12).…”
Section: Clinical Relevancementioning
confidence: 99%
“…However, the cell response to injury does not completely reflect changes in intact lungs (40). Studies in clinical patients with BPD and animal models have demonstrated abnormal expression of some cytokines, such as insulin-like growth factor-I (IGF-I) (30,38), transforming growth factor (TGF)-␤1 (3,37,52), keratinocyte growth factor (KGF) (20,25), and bone morphogenetic protein (BMP) (3), which play regulatory roles in the AEC transdifferentiation process (7,10,26,44,63). These data support our hypothesis that abnormal transdifferentiation may be involved in BPD pulmonary epithelial injury.…”
mentioning
confidence: 99%